2002
DOI: 10.1029/2000jd000081
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variability of tropospheric ozone (O3) in the boundary layer above the Aegean Sea (eastern Mediterranean)

Abstract: [1] To study the spatial and temporal variability of tropospheric ozone in the marine boundary layer over the Aegean Sea (eastern Mediterranean), an O 3 analyzer has been installed onboard of a passenger vessel traveling on a regular basis in the Aegean Sea (from Heraklion/Crete 35°30 0 N, 25°13 0 E to Thessaloniki 40°64 0 N, 22°97 0 E) during a period of 14 months (August 1999 to November 2000. In addition, O 3 data have been obtained on a daily basis at the regional background station of Finokalia (Crete; 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
67
0
16

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 22 publications
11
67
0
16
Order By: Relevance
“…The area under study is characterized by particularly enhanced level of pollutants by means of ozone Kouvarakis et al, 2002;Kondratyev and Varotsos, 2002;Gerasopoulos et al, 2005;2006a) and particulate matter (Gerasopoulos et al, 2003(Gerasopoulos et al, , 2006b) that also influence the fraction of solar irradiance reaching the surface Papayannis et al, 1998;Varotsos et al, 2001). Total solar eclipses enable the evaluation of our understanding of air pollution build-up and of the response of the gas-phase chemistry of photo-oxidants during a drastic perturbation in solar radiation.…”
Section: Photochemistrymentioning
confidence: 99%
“…The area under study is characterized by particularly enhanced level of pollutants by means of ozone Kouvarakis et al, 2002;Kondratyev and Varotsos, 2002;Gerasopoulos et al, 2005;2006a) and particulate matter (Gerasopoulos et al, 2003(Gerasopoulos et al, , 2006b) that also influence the fraction of solar irradiance reaching the surface Papayannis et al, 1998;Varotsos et al, 2001). Total solar eclipses enable the evaluation of our understanding of air pollution build-up and of the response of the gas-phase chemistry of photo-oxidants during a drastic perturbation in solar radiation.…”
Section: Photochemistrymentioning
confidence: 99%
“…In the Mediterranean, the background surface ozone mixing ratios are the highest in Europe (Kouvarakis et al 2000(Kouvarakis et al , 2002Gerasopoulos et al 2005;Nolle et al 2002;Lelieveld et al 2002). According to Nolle et al (2005), the ozone mixing ratio in the Central Mediterranean might have increased by a factor of five over the last century.…”
Section: Introductionmentioning
confidence: 99%
“…Previous campaigns combined airborne measurements of particles and gases, measurements from ships and measurements at land-based stations including Finokalia, and they showed that measurements at Finokalia are representative of the background Eastern Mediterranean atmosphere (Kouvarakis et al, 2002;Lelieveld et al, 2002). As such, this study provides insights about aerosol in the Eastern Mediterranean as well as the transport and evolution of organic aerosol in general.…”
Section: Introductionmentioning
confidence: 99%